University Lecturers’ Perceived Usefulness of Mobile Technology for Instruction in Kwara State, Nigeria - Ahmed Idris Issa; Joy Abosede Peter; Mukhtar Adeola Ibrahim; Muftau Kayode Salaudeen; Simon Ayoola Taiwo; Kehinde Murtala Nuhu; Falade Ayotunde Atanda (Scientia Publica Media, 2026)
Even though mobile technologies are highly evolved, their advantages and capabilities have not been fully utilized in education, particularly in underdeveloped nations like Nigeria. Therefore, this study examined how university lecturers in Kwara State, Nigeria, perceived the use of mobile technology for teaching. The study used the quantitative method of descriptive research. Three Kwara State universities were purposefully chosen to provide the sample. Using a proportionate and stratified random sample procedure, 315 respondents were chosen. Data was gathered using a questionnaire modified by the researchers. Frequency counts, percentages, and means were used to address the study topics, while t-tests and ANOVA were employed to assess hypotheses at the 0.05 level of significance. The results indicated that university lecturers held favorable perceptions regarding the instructional usefulness of mobile technologies. Statistical analysis revealed no significant differences in lecturers’ perceived usefulness of mobile technology for instructional purposes (F(19, 295) = 0.68, p = 0.84). Additionally, lecturers’ perceptions did not differ significantly based on gender. No significant differences were also found in perceived usefulness with respect to educational qualifications (F(19, 295) = 1.56, p = 0.07) or area of specialization (F(19, 295) = 1.06, p = 0.39). The study concluded that university lecturers had a positive perception of the use of mobile technologies for instruction in Kwara State, Nigeria, and has great potential if it is adopted for instructional delivery. It was recommended that the university’s lecturers should be provided with mobile technologies and encouraged to utilize them for instruction, as it will lead to more active and innovative teaching methods.